Xã hội hóa hoạt động thông tin-thư viện tại Cục Thông tin Khoa học và Công nghệ Quốc gia - Trần, Thị Hải Yến (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Explains concept of socialization and its role in S&T library, information and statistics activities; presents some initial results in socialization of library and information activities at NASATI; puts forward solutions to intensifying these activities